WHO DOESN’T WANT TO BE SATISFIED IN LIFE? TESTING A STRUCTURAL EQUATION MODEL BASED ON PSYCHOLOGICAL WELL-BEING - Dhingra, Manish; Dhingra , Vaishali; Mudgal, Rakesh K. (International Journal of Psychosocial Rehabilitation, 2020)
Who doesn’t want to be dissatisfied in this world? None! So, if satisfaction is that important, we need to understand the variables which should be focused upon so that more and more people can become satisfied. The aim of this research is to explore the relationship between the constructs related with Psychological Well-being and Satisfaction with Life using the scales developed by Diener in 2009 and 1985 respectively. Usage of a common term by people for valuing different aspects related to their life, body and mind, the events taking place and the circumstances in which they live, led to a convergence between these constructs related to happiness (Diener et al, 2006). The relationship between psychological well being, and Satisfaction with Life was examined using Structural Equation Model (SEM). The scales are adopted from (Diener, 2009); Lyubomirsky & Lepper (1999).The participants in this research were 212 students studying in university. Standardized beta in the Structural Equation Model showed that the most significant predictor of Psychological well being was “I lead a purposeful and meaningful life” and of Satisfaction with life it was “The conditions of my life are excellent”. Results have been discussed in accordance with the related literature.